The Effect Of Disease Prevention Motivation Program On Family Caregivers’ Behavior In Oral Health Care For Preschoolers With Congenital Heart Disease - ใจอารีย์, ผุสดี; จีระแพทย์, วีณา (Journal of The Royal Thai Army Nurses, 2018)
This quasi-experimental research investigated the effect of disease prevention motivation program on family caregivers’ behavior in oral health care among preschoolers with congenital heart disease. The protective motivation theory by Rogers [1983] was applied for the program development. Subjects consisted of 44 family caregivers of the preschoolers with congenital heart disease, aged between 3-6 years admitted at an inpatient unit of two tertiary level hospitals. They were equally assigned into either the control group or the experimental group, 22 in each group. The experimental group received the motivation enhancing program for 4 weeks while the control received the conventional nursing care. Research instruments included the motivation enhancing program, the experimental monitoring questionnaire (EMS) and the family caregivers’ behavior in oral health care among preschoolers with congenital heart disease questionnaire (FCB-OHCPCHDS). Data were analyzed using descriptive statistics and t-test. The major results are as follows: 1. The mean score of family caregivers’ behavior in oral health care among preschoolers with congenital heart disease after receiving the motivation enhancing program was higher than that before receiving the program at significant level .05. 2. The mean score of family caregivers’ behavior in oral health care among preschoolers with congenital heart disease in the group receiving the motivation enhancing program was higher than that in the group receiving routine nursing care at a significant level of .05.